Subclinical infection caused by a recombinant vaccine-like strain poses high risks of lumpy skin disease virus transmission - Shumilova, Irina; Prutnikov, Pavel; Mazloum, Ali; Krotova, Alena; Tenitilov, Nikita; Byadovskaya, Olga; Chvala, Ilya; Prokhvatilova, Larisa; Sprygin, Alexander (Frontiers in Veterinary Science, 2024)
LLumpy skin disease (LSD) is a transboundary viral infection, affecting cattle with characteristic manifestations involving multiple body systems. A distinctive characteristic of lumpy skin dis-ease virus is the subclinical disease manifestation wherein animals have viremia and shed the virus through nasal and ocular discharges, while exhibiting no nodules but enlarged lymph nodes that are easily oversighted by inexperienced vets. Further research on the role of subclin-ically ill animals in the transmission of LSD virus (LSDV) can contribute to the development of more effective tools to control the disease worldwide. Thus, this study aims to determine the potential role of subclinical infection in virus transmission in a non-vector-borne manner. To achieve this, we inoculated animals with the recombinant vaccine-like strain (RVLS) Udmurti-ya/2019 to cause clinical and subclinical LSDV infection. After the disease manifestation, we re-located the subclinically ill animals to a new clean facility followed by the introduction of an-other five animals to determine the role of RVLS-induced subclinical infection in the virus transmission via direct/indirect contact. After the introduction of the naïve animals to the relo-cated subclinically ill ones in a shared airspace, two introduced animals contracted the virus (clinically and subclinically), showing symptoms of fever, viremia, and seroconversion in one animal, while three other introduced animals remained healthy and PCR-negative until the end of the study. In general, the findings of this study suggest the importance of considering LSDV subclinical infection as a high-risk condition in disease management and outbreak investiga-tions.